Elaborasi Green Marketing dan Islamic Marketing Ethics (Studi Kasus UMKM di Indonesia) - zuhdan ady fataron (ITB AAS INDONESIA Surakarta, 2022)
Islam contains teachings that emphasize the value of morality in every behavior, including in conducting business activities. Business ethics need to be based on good values in the Qur'an. These good values are respect, protect, and the environment. Along with the activities of UMKM in Indonesia, the potential for natural damage also increases if their business activities do not promote environmentally friendly businesses. Marketing companies that have the necessary values in the era of environmental awareness will attract more consumers. This study uses an approach with analytical descriptive analysis, with the aim of examining the combination of ethical values of Islamic marketing and green marketing in the business of UMKM. The results of the study found that specifically the green marketing concept can be realized in the concept of Islamic marketing ethical values. The two marketing concepts have similarities in social responsibility and environmental value-based marketing. Elements of green marketing that are in accordance with Islamic business ethics values include green products, green prices, green places, and green promotions. The elaboration of Islamic marketing ethics and green marketing shows the commitment of business actors in meeting consumer needs, wants, and desires in the era of sustainable development.